'Studying and working enriches my career'. (22nd September 2018) - Unknown
Abstract : Vet Ian Glover describes how he fitted studying for a diploma in bovine health management alongside clinical work. Here, he reflects on his career, the skills he has learnt and the advice he would pass on.